A 10-bit wide-band CMOS direct digital RF amplitude modulator. - Yijun Zhou
This paper describes a low-distortion wide-band CMOS direct digital RF amplitude modulator, which uses a 10-bit linear interpolation current-steering digital-to-analog converter (DAC) and a Gilbert-cell-based mixer to generate an amplitude modulated RF signal directly. The linear interpolation increases the attenuation of the DAC's image components. The reconstruction filter is, therefore, eliminated. The DAC's differential current signals are directly sent to the mixer, which improves the linearity of the modulated RF signal. Thus, the RF transmitter structure is simplified, and the low distortion is achieved. This modulator is suitable for system-on-chip (SOC) design and is easily scalable. The chip was fabricated in a 0.35-μm 3.3-V double-poly triple-metal CMOS process. The core size of the chip is 0.52 mm×0.68 mm. With a 3.3-MHz modulation signal, a 50-MHz clock, and a 1-GHz carrier, the distortion components are below -53.81 dBc, and the attenuation of the image signal is 47.45 dB. The output power is -6.5 dBm, and the total power consumption is 159.8 mW.
Keywords: 0.35 micron; 10 bit; 159.8 mW; 3.3 V; Gilbert cell mixer; RF transmitter; Image attenuation; Linear interpolation current-steering digital-to-analog converter; Low-distortion wide-band CMOS direct digital RF amplitude modulator; System-on-chip.